2022
DOI: 10.3389/fmars.2022.945758
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Largest Deep-Sea-Endemic Teleost Fish at Depths of Over 2,000 m Through a Combination of eDNA Metabarcoding and Baited Camera Observations

Abstract: The Yokozuna Slickhead Narcetes shonanmaruae is a recently described deep-sea fish species and an active-swimming, relatively large top predator in Suruga Bay, Japan. Its only known habitat is the deepest part of the bay (>2,000 m); six individuals have been collected thus far (up to 138 cm in total length). During our monitoring survey of faunal diversity on seamounts within marine protected areas in Japanese waters, environmental DNA (eDNA) metabarcoding revealed the Yokozuna Slickhead 12S ribosomal R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…On the other hand, a few surveys of aquatic communities in the deep sea have been conducted (Fraija-Fernańdez et al, 2020;McClenaghan et al, 2020;Merten et al, 2021). Recently, a combination of eDNA with other methodologies (e.g., imaging data) is shown to be a more comprehensive method of monitoring deep-sea biodiversity (Fujiwara et al, 2022;Stefanni et al, 2022). However, it is estimated that in the deep sea, where biomass is low, the amount of eDNA sources is lower than in coastal and surface seawater (McClenaghan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a few surveys of aquatic communities in the deep sea have been conducted (Fraija-Fernańdez et al, 2020;McClenaghan et al, 2020;Merten et al, 2021). Recently, a combination of eDNA with other methodologies (e.g., imaging data) is shown to be a more comprehensive method of monitoring deep-sea biodiversity (Fujiwara et al, 2022;Stefanni et al, 2022). However, it is estimated that in the deep sea, where biomass is low, the amount of eDNA sources is lower than in coastal and surface seawater (McClenaghan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental DNA analysis is an emerging tool for deep-sea biodiversity [25][26][27] and ecological studies [28][29][30] , yet eDNA is less abundant in the deep-sea, such that larger volumes of water are needed to attain representative samples, and the manual labour required to filter those samples in situ can become a limitation 31 . Furthermore, remote, deep-sea habitats are expensive to reach in the first place, so leveraging of natural samplers in this context represents a major boost for large scale ocean exploration and monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…A major advantage of the lander is that it can explore fauna behavior, including the interactions between species. It is a powerful tool for the detection of rare predatory sh species (Fujiwara et al, 2022), which are di cultly found through physical sampling. The structure of the community should be visually determined to better understand vulnerable marine ecosystems.…”
Section: Observation Advantages and Limitations Of The Landermentioning
confidence: 99%